STUDY OF VARIABLES SIGNIFICANCE AND OPTIMIZATION TO REDUCTIVE LEACHING PARAMETERS OF BANGKA PRE-OXIDIZED ILMENITE IN HYDROCHLORIC ACID USING ANOVA AND TAGUCHI METHODS TO PRODUCE SYNTHETIC RUTILE - Gefien Imami, Tio
Rutile is used as a raw material in the pigment industry and in the Kroll process which requires feed with titanium dioxide levels above 90%. However, due to the lack and depletion of natural rutile in nature, ilmenit upgrading to produce synthetic rutile become promising in order to substitute the industrial need for rutile. The process of rutile extraction from ilmenite mineral can be carried out either by the pyrometallurgical route through melting to produces titanium-rich slag or by the hydrometallurgical route through leaching in acidic solutions, separation of iron and titanium and titanium recovery. In this study the effect of pre-oxidation and reductive leaching on the performance of Bangka ilmenite leaching in hydrochloric acid was studied. Analysis by the Taguchi and ANOVA methods was carried out to optimize the process and determining the significance and contribution of leaching variables to the extraction percentage of Fe and Ti. The experimental work was started with the preparation, sampling, and characterization of the initial ilmenite sample by using XRD, mineragraphy, and XRF analyses. Preliminary experiments were carried out to determine the optimal temperature to oxidize ilmenite that yields rutile and hematite. Afterward, a series of leaching experiment was conducted using the Taguchi orthogonal array L'16 (45), that uses 5 leaching variables, each with 4 levels. Variables that were kept constant in the leaching experiment were stirring speed of (700 rpm), volume of HCl solution (200 ml), and Fe°/Ilmenite mass ratio of 1/5. The leaching variables which were studied are HCl concentration, leaching temperature, solid-liquid ratio, ilmenite size fraction, and leaching time. Optimum temperature for oxidation was obtained at 700°C, for 6 hours. The leaching variables that have significant effect to Fe extraction are leaching temperature, solid-liquid ratio, HCl concentration, and ilmenite size fraction. The leaching duration at the range studied did not significantly affect extraction percentages of iron and titanium. The leaching variables that significantly affect titanium extraction are in the order of: solid-liquid ratio, HCl concentration, temperature, size fraction, and leaching time. Optimal leaching condition was obtained at 6M HCl concentration, temperature 80°C, S/L ratio 1/20, ilmenite size fraction of -200 +325#, 6-hour leaching time, with iron and titanium extraction percentages of 98.07% and 11.35%, respecively. Selectivity of Fe leaching to Ti under optimum condition reached 0.9 (out of 0-1 scale). The ilmenite leaching residues under optimal conditions contains 92.6% of rutile (TiO2), 2.9% of hematite (Fe2O3), and 2.5% of cassiterite (SnO2).